1998
DOI: 10.1165/ajrcmb.18.1.2627
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin 13 by Alveolar Macrophages from Normal and Fibrotic Lung

Abstract: Human interleukin 13 (IL-13) is a cytokine that has a profound effect on primary immune cells by inducing immunoglobulin production, proliferation of B cells, and the differentiation of cells of the monocytic lineage. IL-13 can inhibit the production of inflammatory cytokines by both macrophages and monocytes. Previously, IL-13 expression has been reported only in cells of the T-cell lineage and the mast cell line HMC-1. We now report the presence of IL-13 mRNA and protein in human alveolar macrophages (AMs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
155
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(167 citation statements)
references
References 19 publications
(12 reference statements)
10
155
1
1
Order By: Relevance
“…Exaggerated levels of IL-13 production have been implicated in the pathogenesis of a variety of disorders, including asthma, chronic obstructive pulmonary disease, pulmonary fibrosis, scleroderma, hepatic fibrosis, and nodular sclerosing Hodgkin's disease (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The remarkable effects that IL-13 can have in these disorders can be appreciated in studies that highlighted the ability of IL-13 to induce tissue inflammation, cathepsin-and MMP-mediated proteolysis, and TGF-␤1-induced tissue fibrosis (25,32,48).…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated levels of IL-13 production have been implicated in the pathogenesis of a variety of disorders, including asthma, chronic obstructive pulmonary disease, pulmonary fibrosis, scleroderma, hepatic fibrosis, and nodular sclerosing Hodgkin's disease (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The remarkable effects that IL-13 can have in these disorders can be appreciated in studies that highlighted the ability of IL-13 to induce tissue inflammation, cathepsin-and MMP-mediated proteolysis, and TGF-␤1-induced tissue fibrosis (25,32,48).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is nicely illustrated in studies from our laboratory and others that demonstrate that IL-13 is a potent stimulator of eosinophil-, macrophage-and lymphocyte-rich inflammation, mucus metaplasia, tissue fibrosis, and parenchymal proteolysis (5)(6)(7). In accord with these observations, IL-13 dysregulation has been documented, and IL-13 has been implicated in the pathogenesis of a variety of diseases characterized by inflammation and tissue remodeling including asthma, scleroderma, idiopathic pulmonary fibrosis, viral pneumonia, hepatic fibrosis, nodular sclerosing Hodgkin's disease, and chronic obstructive pulmonary diseases (COPD) (1)(2)(3)(4)(7)(8)(9)(10)(11)(12)(13). Studies from our laboratory and others have demonstrated that IL-13 mediates its tissue effects by activating a broad array of downstream target genes including chemokines, matrix metalloproteinases (MMPs), transforming growth factor (TGF)-␤ 1 , and chitinases (6, 14 -17).…”
mentioning
confidence: 84%
“…Subsequent studies demonstrated that IL-13 and IL-4 play distinct roles in biology with IL-4 contributing to Th2 cell differentiation and response generation, whereas IL-13 contributes as a major effector of Th2 inflammation and tissue remodeling (1)(2)(3)(4). The latter is nicely illustrated in studies from our laboratory and others that demonstrate that IL-13 is a potent stimulator of eosinophil-, macrophage-and lymphocyte-rich inflammation, mucus metaplasia, tissue fibrosis, and parenchymal proteolysis (5)(6)(7). In accord with these observations, IL-13 dysregulation has been documented, and IL-13 has been implicated in the pathogenesis of a variety of diseases characterized by inflammation and tissue remodeling including asthma, scleroderma, idiopathic pulmonary fibrosis, viral pneumonia, hepatic fibrosis, nodular sclerosing Hodgkin's disease, and chronic obstructive pulmonary diseases (COPD) (1)(2)(3)(4)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 88%
“…Ratios of IL-18:␤-actin, TNF␣:␤-actin and IL-10:␤-actin were calculated for semiquantitative RNA expression analysis as previously described. 20 …”
Section: Densitometric and Semi-quantitative Pcr Analysismentioning
confidence: 99%